ANALYSIS OF ROADHEADER PERFORMANCE FOR TUNNEL RAILWAY CONSTRUCTION IN PURWOKERTO-KROYA LINE IN NOTOG - WISHNU PRADANA (NIM : 12113086), YOGA
The railway tunnel at Notog is one of the double track railway tunnels that belong to the Purwokerto-Kroya line, Central Java. The tunnel will be built along 471 meters by using of a roadheader digging tool. One of the important faktors in the tunnel construction process is the excavation activity which is the initial activity of the tunnel construction cycle. Therefore, the planning and execution of the excavation should be considered well. Planning of excavation activities includes the selection of tunnel construction methods, the selection of digging tools, and prediction of productivity of the digging tool. In the making of this Notog tunnel, using New Austrian Tunneling Method (NATM) with the main digging tool is a roadheader. The prediction of roadheader productivity is calculated based on the Bilgin equation (1990), Kramadibrata (1996), and Copur (1998) using various parameters, such as rock compressive strength, rock tensile strength, RQD, spacing discontinuities, rock density, power of digging tool, and weight of digging tool. This prediction value is then compared with aktual productivity in the field for analysis and evaluation. The results of the analysis of predictions and aktual results in the field found that roadheader performance against clay rock in the field is better than performance against volcanic breccia. The results showed the stronger the rocks productivity of the roadheader productivity will decrease. The results of the prediction show that the Copur equation (1990) is suitable for predicting roadheader productivity in weak rocks, while Kramadibrata equation (1996) and Bilgin (1998) is more suitable for predicting roadheader productivity in strong rocks.